Rural labor migration and household waste separation willingness: Evidence from 6849 rural residents in China - Yi Yu; Dan Pan (PLoS ONE, 2025)
Understanding the key determinants of rural household waste separation willingness (HWSW) is indispensable in promoting sustainable development for many developing economies. Few studies have been dedicated to examining the impact of large-scale rural labor migration (RLM) on HWSW in rural China. Based on a nationwide sample including 6849 rural residents, this paper investigates the relationship between RLM and rural residents’ HWSW. The generalized propensity score (GPS) method and the instrumental variable (IV) approach are used to account for potential selection bias and endogenous problems. The results show that RLM inhibits rural residents' HWSW. Specifically, with every 1% increase in RLM, the likelihood of rural residents’ HWSW will decrease by 3.5%. This effect remains significant after a series of robustness checks. Heterogeneity analysis reveals that the negative impact of RLM on HWSW is larger for rural residents who live in Midwest China, with low education and less income. Further mechanism analysis shows that RLM reduces rural residents’ HWSW by decreasing their social capital, undermining their rural community administration, and diminishing their village's collective economic income.